Synthesis of alkali free MG-AL layered double hydroxide catalyst via hydrothermal reconstruction method for biodiesel production of waste cooking oil / Erma Hafiza Ibrahim @ Abd Aziz - Ibrahim @ Abd Aziz, Erma Hafiza (2021)
Biodiesel has attracted a great deal of attention worldwide because of its biodegradable, nontoxic, clean and renewable characteristics. It was produced via transesterification of vegetable oil with methanol in the presence of homogeneous and heterogeneous catalyst. Some of the challenges in this process are the high cost of biodiesel feedstock and the alkali catalyst that can contribute to saponification problem. In this study, the Mg-Al layered double hydroxide (LDH) with varying the Mg/Al ratios were prepared by alkali free co-precipitation method. Different Mg/Al ratios which were 2:1, 3:1 and 4:1were used in the synthesis of Mg-Al LDH precursors. Then, the precursors were thermally decomposed at 450 ⁰C and the derived mixed oxides reconstruct back to layered structures using hydrothermal reconstruction method. The results show that the physicochemical properties of the synthesized catalysts (precursors, mixed oxides and reconstructed LDH) weakly depend on the Mg/Al ratios. XRD pattern for precursor show fingerprint pattern of LDH. This pattern loss after calcination and appeared again after reconstruction indicated that the hydrothermal treatment was successfully restored the LDH structure. The catalytic activity of the reconstructed Mg-Al LDH was further evaluated in the biodiesel production from waste cooking oil (WCO) at the identified reaction conditions. Optimum operating conditions were established through response surface methodology (RSM) for promising options. It is observed that Mg-Al LDH for molar ratio 4:1 is the most active catalyst which gives the best biodiesel yield of 37.45 % using 34:1 methanol to oil ratio after 11.9 h at reaction temperature 68.3 ⁰C and catalyst loading 1.125 %. Moreover, the fuel properties of the prepared biodiesel from the WCO at the optimal process conditions have been found to comply with the ASTM and EN standard specifications.